Chavdar Tzochev. The Athenian Agora Volume XXXVII. Amphora Stamps from Thasos. - van der Enden, Mark (Journal of Greek Archaeology, 2017)
Chavdar Tzochev’s Amphora Stamps from Thasos is an excellent addition to the Athenian Agora Series and an exhaustive study of an important material category, so abundantly attested at the Agora. T’s book not only consists of a detailed discussion of the typology and chronology of Thasian amphora stamps but also is an attempt to interpret the distribution of the stamps within a wider socio-economic context. Clearly laid out and expertly presented, the book equally serves as an excellent introduction to amphora stamps from Thasos more generally. The book as such is not only of interest to the amphora stamp specialist but would also appeal to a more general audience interested in the wider socio-economic importance of Thasian amphorae and the practices associated with stamping. T., therefore, succeeds marvellously in presenting and discussing a highly specialist data-set in such a way as to be of interest to specialists and more general readers alike.